Addressing Practice-Based Learning: An Examination of an Online Course to Assess Residents' Training in Education - Scott Cottrell (Association of American Medical Colleges, 2006)
Abstract Introduction Teaching is an important skill that is addressed in the Accreditation Council for Graduate Medical Education (ACGME) competency framework. Research has demonstrated that residents can spend as much as 25% of their time teaching, and receive as much as 40% of their training from peers. It is important, then, to prepare residents to become informed teachers, who will partner with other educators to ensure the future and quality of medical education. ACGME characterizes teaching as a practice-based learning and improvement competency that is defined as facilitating the learning of students and other healthcare professionals. Methods The purpose of this resource is to provide the materials used for an online course: Residents as Teachers. Medical educators may use or tailor this online course to address residents' teaching skills. An investigation was conducted to explore the course's potential to help further residents' knowledge of teaching and learning issues. Each resident received a pre-/postcourse survey evaluating the residents' knowledge of educational theory, assessment of student learning, and educational research. The residents also self-reported their level of interest and motivation about teaching. Data was analyzed by a two-way, repeated-measures analysis of variance using survey (pretest vs. posttest) and resident group (surgical vs. medical) as variables in the model along with their interaction. Results Residents self-reported spending a higher percentage of their time teaching in a clinical setting versus a classroom setting. There was no significant difference between surgical and medical resident groups. Time spent teaching in a clinical setting was 17.8% and 14% for surgical and medical residents, respectively, while time spent teaching in the classroom was 5.48% and 4.57%. After taking the online teaching course, knowledge of educational theory, assessment, and research was significantly (p < .01) enhanced with no difference between resident groups. Although residents self-reported significantly (p < .05) greater interest and motivation about teaching after completing the online course, the low effect size of 0.26 would indicate practical limitations of this course in altering attitudes toward teaching. Discussion Overall, the study suggests that medical residents will improve their understanding of educational theory, assessment, and research with online instruction. While the course enhanced residents' interest, it may be limited and additional learning experiences may be required to further enhance residents' attitudes about teaching. This study supports the efficacy of online instruction to improve residents' knowledge and interest toward teaching and offers a practiced-based approach to meeting teaching competencies set forth by the ACGME.